Modern View on Microbiocenosis, Immune Response and Factors Influencing on Their Formation. Fundamental and Applied Aspects - N. M. Bogdanova; E. M. Bulatova; M. N. Wasia ("Paediatrician" Publishers LLC, 2013)
This review of current literature summarizes results of scientific studies on the structure of the intestinal microbiota both of adults and infants. It is shown, that all intestinal microbiota of an adult consists of 395 phylogenetically isolated groups of microorganisms, among them 244 are absolutely new. Based on the RNA-sequencing of genes the most common among Caucasians enterotypes were detected. It was demonstrated, that specific structure of intestinal microbiota of an adult individual is unique and stable and that genetic background of the macroorganism is a base of intestinal microbiome formation. The article covers the issues of special characteristics of microbiocenosis development at the early stages of ontogenesis. It is emphasized, that prevalence of «infantile» species of bifidobacteria in the structure of intestinal microbiota of breast-fed infants is due to the presence of certain nutritive substances in the milk: oligosaccharides of the breast milk, which are natural prebiotics. The authors give criteria for including the nutrients into the group of prebiotics and show new experimental and clinical data on influence of prebiotics on different levels of immunological defense system.Key words: intestinal microbiota, enterotypes, prebiotics, oligosaccharides, inulin, immune response.